1983
DOI: 10.1099/00221287-129-1-51
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis of Drug-induced Changes in Na+ and K+ Contents of Single Bacterial Cells

Abstract: Time-dependent changes in the intracellular Na+/K+ ratio of Escherichia coli, induced by the nitrofuran derivative HN32 [2,4-diamino-6-(5-nitrofuryl-2)-5-ethylpyrimidine], were measured by laser-induced mass spectrometry of single bacterial cells. The results show good agreement with data on viable cell and total cell counts, release of ATP and 14CO2 production demonstrating that the single cell analysis of intracellular sodium and potassium concentrations may supply reliable information on cell viability and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Details of the technique and the mass spectrometric determination of viability have been described previously (36). For cultivable bacteria, we showed that the physiological states (viabilities) determined by mass spectrometric analysis of the cation ratios agreed well with those determined by established microbiological techniques (17,30,37) and, in the case of M. lepraemurium, with those determined by the mouse footpad assay (13).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Details of the technique and the mass spectrometric determination of viability have been described previously (36). For cultivable bacteria, we showed that the physiological states (viabilities) determined by mass spectrometric analysis of the cation ratios agreed well with those determined by established microbiological techniques (17,30,37) and, in the case of M. lepraemurium, with those determined by the mouse footpad assay (13).…”
supporting
confidence: 64%
“…The mass spectrometric analysis of intrabacterial Na ϩ -to-K ϩ ratios of individual bacterial organisms is routinely used in our laboratory to monitor the effects of drugs on bacterial viability (10,12,13,17,29,30,36,37). Since this method renders information independent from the ability of the bacterial organisms to multiply in vitro, it saves time and labor in the case of slowly growing cultivable mycobacteria and, moreover, can also be used in the case of the noncultivable species M. leprae.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of SCMS in the late 1970s, laser ablation (LA) was used to produce ionic species from tissues and cell cultures [5]. In 1981, LA‐MS was used to determine the physiological state of individual bacterial cells by analyzing sodium/potassium concentration ratios [6, 7]. The LA‐MS instrument was a laser microprobe mass analyzer (LAMMA 500), developed by F. Hillenkamp and M. Karas, who were the first to report MALDI in 1988 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatotoxicity implies chemical-driven liver damage and it is the most common reason for a drug to be withdrawn from the market with more than 900 drugs implicated in causing liver injury [23]. Hepatotoxicity and drug-induced liver injury also account for a substantial number of compound failures, highlighting the need for drug screening assays, such as stemp cell-derived hepatocyte-like cells, that are capable of detecting toxicity early in the drug development process [18]. Hepatotoxicity data were used to build a number of QSTR models to identify the structural features of compounds correlated to their hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%